Estimation of Production Function of Hiunde (Boro) Rice - Bhujel, RB; Ghimire, SP (Nepal Agriculture Research Journal, 2009)
Hiunde (Boro) rice has not been popularized due to least attention given to this crop in Nepal. Inorder to estimate the production function of this crop, a field survey in Morang district during2002/2003 was carried out using a semi-structured questionnaire. The primary information wascollected through face to face interview. The result of the empirical model of Cobb-Douglasproduction function revealed the model significant at 1% level and defined 95% variation inHiunde rice production due to variation in independent variables included in the model. Thecoefficient of area, nitrogen, phosphorous, and tractor hour were found significant at 1% levelwhile the dummy for more than 10 times of irrigation was significant at 5% level and up to 10times of irrigation and potash was significant at 10% level. The effect of human and bullocklabor was found non-significant. Among the sampled farmers the average cropping intensity was194% and average yield of Hiunde rice was 4802.50 kg/ha. On an average 131 kg of nitrogen,phosphorous and potash was applied for one ha and 15 irrigations in average. The net benefitfrom Hiunde rice was found to be Rs. 14507.41/ha with 1.73 benefit cost ratio. About 31% costwas incurred in land preparation and transplanting which was highest among the operations. Itwas followed by the costs incurred in fertilizers and agrochemicals which counted 23%.Key words: Estimate; Hiunde rice; production functionDOI: 10.3126/narj.v7i0.1874Nepal Agriculture Research Journal Vol.7 2006 pp.88-97